Neuromuscular Training Targeted at Improving Performance on the Posterolateral Component of the Y-Balance Test : Does This Translate to Decreased Knee Valgus Moments During Unplanned Sidestepping? - Loh, Darius Wei Jing (2017)
Non-contact anterior cruciate ligament (ACL) injuries occurring from an unplanned sidestep cut in netball are four to six times more likely in females than male athletes. A previous unpublished study from the Singapore Sports Institute found a negative correlation between the posterolateral (PL) reach scores of the Y-balance test (YBT), an inexpensive screening tool to predict injuries due to poor neuromuscular control, and peak knee valgus moments (KVM) during unplanned sidestepping. Therefore, this study aims to assess the effects of a customized neuromuscular training program (NMTP) targeted at improving the PL reach scores of the YBT, and translating to decreased peak KVM during unplanned sidestepping, potentially reducing non-contact ACL injury risks. The NMTP was hypothesized to reduce externally applied peak KVM, and the associated flexion and internal rotation moments during unplanned sidestepping. Singapore National female netballers (9 experimental, 9 control) participated in a series of sidestep cuts and YBT in a randomised order. Knee moments during weightacceptance phase was obtained using a 12-camera three-dimensional motion capture system. Following a 6-8 week NMTP consisting of plyometric, balance, strength-balance hybrid and flexibility components, there were significant main effects on the posteromedial (p = 0.008; ^2 = 0.365), posterolateral reach scores (p = 0.004; ^2 = 0.393), composite scores (p = 0.007; ^2 = 0.365) and flexion moments (p = 0.018; ^2 = 0.301). These findings suggest that this customised NMTP can reduce externally applied flexion moments, and potentially internal rotation moments as well as maintaining peak KVM during an unplanned sidestep cut over a sporting season.